2022
DOI: 10.1097/qai.0000000000002906
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of HIV-1 Subtype Diversity on Long-Term Clinical Outcomes in Antiretroviral Therapy in Guangxi, China

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This study found that PLWH infected with CRF01_AE had worse CD4(+) T cell count recovery than that infected with CRF07_BC, which was mainly due to the higher percentage of X4 gonotropic virus. 6 , 7 In addition, the CD4(+) T cell count recovery rate of PLWH infected with CRF85_BC was lower than that of PLWH infected with CRF07_BC. As the subtype of the virus is currently mainly prevalent among the heterosexually transmitted elderly people in southern Sichuan, 7 it is once again emphasized that the virus is needed to pay close attention of the health department.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This study found that PLWH infected with CRF01_AE had worse CD4(+) T cell count recovery than that infected with CRF07_BC, which was mainly due to the higher percentage of X4 gonotropic virus. 6 , 7 In addition, the CD4(+) T cell count recovery rate of PLWH infected with CRF85_BC was lower than that of PLWH infected with CRF07_BC. As the subtype of the virus is currently mainly prevalent among the heterosexually transmitted elderly people in southern Sichuan, 7 it is once again emphasized that the virus is needed to pay close attention of the health department.…”
Section: Discussionmentioning
confidence: 98%
“…6 , 7 In addition, the CD4(+) T cell count recovery rate of PLWH infected with CRF85_BC was lower than that of PLWH infected with CRF07_BC. As the subtype of the virus is currently mainly prevalent among the heterosexually transmitted elderly people in southern Sichuan, 7 it is once again emphasized that the virus is needed to pay close attention of the health department. It is necessary to strengthen the prevention and control of AIDS among people infected with the virus, reduce the spread of the virus, and formulate effective measures to strengthen the treatment quality of PLWH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The risk of transmission of newly reported HIV infections infected of the subtype CRF01_AE in this area is higher than that of newly reported HIV infections of the subtype CRF07_BC, while the CD4(+) T-cell recovery of newly reported HIV infections of the subtype CRF01_AE is worse than that of subtype CRF07_BC infections. The main reason for this is the higher proportion of X4 tropic viruses [30,31], which will bring great challenges for the follow-up treatment of newly reported HIV infections of the subtype CRF01_AE. Therefore, the monitoring of subtype CRF01_AE transmission in this area should be strengthened to reduce the prevalence of this subtype in this area.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the impact of HIV-1 subtype diversity on long-term clinical outcomes of ART in Guangxi Province suggested that patients with CRF01_AE may benefit more from immediate ART than those with CRF07_BC. 19 However, studies in southern Nigeria and the UK did not report an association between HIV-1 subtypes and immunological or virological responses after treatment. 20 21 Therefore, we hypothesised that the effectiveness of ART differs among HIV-1 subtypes.…”
Section: Introductionmentioning
confidence: 99%